Perbandingan Bahasa Antara Modern Standard Arabic Dengan Aksen Lebanon - Ahmad Habib Hasani; Choirul Anam; Anang Fauzi; Rika Astari (Alfaz (Arabic Literatures for Academic Zealots), 2021)
This study aims to determine the dialect comparison between Lebanese Arabic (colloquial Arabic) and Fusha Arabic (modern standard Arabic/MSA) so that it can add insight and knowledge about dialect Arabic. This study uses a qualitative descriptive method with a library approach in revealing differences in pronunciation in Fusha Arabic and Lebanese dialects. The results of this study indicate that there are several differences in phonological variations in the pronunciation of Arabic vocabulary. [1] There is a strengthening of the vocabulary sound from أنت (anta) to أنت (enta). [2] The existence of Lenisi as in the wordمعلم becomes معلم . [3] There is a monophthongization of يوم(yauma) to يوم(youma). [4] There is a sound dating as in the word وجه(Wajhu) to وج(wejj). [5] Merging 2 words into one as in the word كيف حالك (kaifa haluka) becomes كيفك(kiifak). [6] The use of French loanwords such as the word بونجور(Bonjur).